ANALISIS PEMBERDAYAAN PEREMPUAN MELALUI HOME INDUSTRY KERUPUK IKAN DI DESA PIASAK KECAMATAN SELIMBAU - Selfi Alfionita; Bambang Genjik; Okianna Okianna (Universitas Tanjungpura, 2021)
AbstractThis study aims to analyze women's empowerment through the fish cracker home industry. Theresearch method used is descriptive method with a qualitative approach. The data sources in thisstudy were women who worked to manage the fish cracker home industry which consisted of 10people as respondents to conduct interviews. Data collection was obtained through observationand interview guidelines, then analyzed using data reduction, data presentation andverification/drawing conclusions, then checking the validity of the data using triangulationtechniques. Researchers conducted observations and interviews with women who work inmanaging the fish cracker home industry 2 times. The results show that the empowermentprocess given to women is in the form of training and then given material on how to process fishcrackers in accordance with health standards and how to process fish crackers clean or hygienicby choosing good quality fish as the basic ingredients for making fish crackers. In addition, inthe empowerment there are mentoring activities which are directive activities by direct guidanceon how to process fish crackers in accordance with the material provided during the training. sothat the women do not find it difficult in the process of making the fish crackers.These mentoringactivities made it easier for women to understand the material that had been given in hands-onpractice to process fish crackers, thus making their production activities smoother and theirbusiness growing.Keywords: Women Empowerment, Fish Cracker, Home Industry